Electrode for all-solid-state battery
By incorporating granules with a core and coating layer of varying conductive materials, the electrical network is optimized, addressing the performance challenges of all-solid-state batteries and enhancing energy density and conductivity.
Patent Information
- Application Number
- JP2024541065
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-09-21
- Filing Date
- 2023-08-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-08-29
AI Technical Summary
All-solid-state batteries face challenges in improving performance due to the need for high ionic conductivity, moisture sensitivity of sulfide-based solid electrolytes, and the requirement for a dense electrode structure to minimize porosity and enhance energy density.
The introduction of granules with a core containing an active material, a first conductive material, and a binder, and a coating layer with a solid electrolyte and a second conductive material, where the first and second conductive materials have different sizes and shapes to form an effective electrical network.
This structure enhances the electrical connectivity within the granules, improving the performance of all-solid-state batteries by increasing energy density and reducing resistance.
Smart Images

Figure 2025502102000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to an electrode for an all-solid-state battery. In particular, the present invention relates to an electrode for an all-solid-state battery comprising granules, the granules comprising a core comprising an active material, a first conductive material and a binder, and a coating layer comprising a solid electrolyte and a second conductive material.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0119465 dated September 21, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference. [Background technology]
[0003] Currently, various batteries capable of overcoming the limitations of lithium secondary batteries are being researched from the standpoints of battery capacity, safety, output, large size, and ultra-compactness.
[0004] Representative examples of batteries that are being continuously researched in both academia and industry include metal-air batteries, which have a much larger theoretical capacity than lithium secondary batteries, all-solid-state batteries, which are safe and have no risk of explosion, supercapacitors, NaS batteries or RFBs (redox flow batteries), and thin film batteries, which are large-sized.
[0005] Among these, all-solid-state batteries refer to batteries in which the liquid electrolyte used in conventional lithium secondary batteries is replaced with a solid, and since they do not use flammable solvents in the battery, there is absolutely no risk of fire or explosion due to the decomposition reaction of conventional electrolytes, which greatly improves safety. In addition, because Li metal or Li alloys can be used as the anode material, there is the advantage that the energy density relative to the mass and volume of the battery can be dramatically improved.
[0006] Sulfide-based solid electrolytes are 10% of all solid electrolytes.-3 ~10 -2 It has a high ionic conductivity of S / cm, is ductile, and has good contact with the interface, which is advantageous for improving resistance, but it is sensitive to moisture, e.g., it generates H2S gas when it comes into contact with water, so it is necessary to create an extremely dry environment during production. In addition, it is necessary to improve the cohesion of the active material and solid electrolyte, and a high-density electrode is required by reducing the porosity.
[0007] Therefore, in order to solve the problems faced in the technical field, the present inventors have continuously studied electrodes for all-solid-state batteries and completed the present invention. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 2016-0146737 Summary of the Invention [Problem to be solved by the invention]
[0009] In order to improve the performance of an electrode for an all-solid-state battery, an electrode for an all-solid-state battery is provided in which granules including a core including an active material, a first conductive material, and a binder, and a coating layer including a solid electrolyte and a second conductive material are introduced as an electrode active material layer. [Means for solving the problem]
[0010] According to a first aspect of the present invention, The battery includes granules including a core including an active material, a first conductive material, and a binder, and a coating layer including a solid electrolyte and a second conductive material, the coating layer being positioned in contact with the outside of the core.
[0011] According to one embodiment of the present invention, the first conductive material and the second conductive material have different sizes or shapes.
[0012] According to one embodiment of the present invention, the first conductive material has an average diameter of 10 nm to 30 nm.
[0013] According to an embodiment of the present invention, the first conductive material has an aspect ratio of 4000 to 6000 and a BET specific surface area of 100 m 2 / g to 300 m 2 / g.
[0014] According to an embodiment of the present invention, the second conductive material has an average diameter of 100 nm to 500 nm.
[0015] According to an embodiment of the present invention, the second conductive material has an aspect ratio of 100 to 300 and a BET specific surface area of 10 m 2 / g to 30 m 2 / g.
[0016] According to an embodiment of the present invention, the first conductive material includes carbon nanotubes.
[0017] According to an embodiment of the present invention, the second conductive material includes carbon nanofibers.
[0018] In an embodiment of the present invention, the active material is a positive electrode active material, and the positive electrode active material is LiCoO2, LiNiO2, LiMnO2, Li2MnO3, LiMn2O4, Li(Ni a Co b Mn c )O2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), LiNi 1-y Co y O2 (0 < y < 1), LiCo 1-y Mn y O2 (0 < y < 1), LiNi 1-y Mn y O2 (0 < y < 1), Li(Ni a Co b Mn c )O4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-z Ni z O4 (0 < z < 2), LiMn 2-z Co z O4 (0 < z < 2) and combinations thereof.
[0019] According to one embodiment of the present invention, the solid electrolyte comprises a sulfide-based solid electrolyte.
[0020] According to one embodiment of the present invention, the granules are spherical particles having a diameter of 30 μm to 150 μm.
[0021] According to one embodiment of the present invention, the weight ratio of the solid electrolyte in the coating layer is 15% by weight to 40% by weight based on the total weight of the granules.
[0022] According to one embodiment of the present invention, the weight ratio of the second conductive material in the coating layer is 0.01% by weight to 1% by weight based on the total weight of the granules.
[0023] According to one embodiment of the invention, the core comprises 85% to 99.8% by weight of active material, 0.1% to 10% by weight of binder, and 0.1% to 10% by weight of the first conductive material, based on the total weight of the core.
[0024] According to one embodiment of the present invention, the weight ratio of the first conductive material to the second conductive material is 5:1 to 30:1.
[0025] According to one embodiment of the present invention, the coating layer is applied and formed on the core by mechanofusion. Effect of the Invention
[0026] An electrode for an all-solid-state battery according to one embodiment of the present invention includes granules including a core including an active material, a first conductive material, and a binder, and a coating layer including a solid electrolyte and a second conductive material, and in the granules, the first conductive material and the second conductive material are adjusted to have different specifications in consideration of the functionality of the core and the coating layer.
[0027] As a result, the granules described above form an excellent electrical network all the way to the inside of the granules even under all-solid-state conditions, and when used as electrodes in all-solid-state batteries, this contributes to improving the performance of the battery. [Brief description of the drawings]
[0028] [Figure 1] FIG. 2 is a schematic diagram showing the shape of a granule according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The embodiments provided in accordance with the present invention can all be achieved by the following description. The following description should be understood as describing preferred embodiments of the present invention, and it should be understood that the present invention is not necessarily limited thereto.
[0030] Unless the measurement conditions and methods are specifically described for the physical properties described in this specification, the physical properties are measured according to the measurement conditions and methods commonly used by those of ordinary skill in the art.
[0031] In one aspect of the present invention, a granule is provided that includes a core containing an active material and a coating layer containing a solid electrolyte. The granule may be used in an electrode for an all-solid-state battery. In order to understand the structure of the granule, FIG. 1 is a drawing that shows a schematic shape of a granule according to one embodiment of the present specification. As shown in FIG. 1, the core (10) is spherical and located inside the granule, and the coating layer (20) is located so as to surround the core. The granule (100) including the core and the coating layer is a spherical particle. Here, the spherical shape does not mean a perfect sphere in the strict sense, but is generally used as a comprehensive concept that includes even round particles. The core includes an active material, a first conductive material, and a binder, and the coating layer includes a solid electrolyte and a second conductive material. The active material in the form of fine particles in a powder state is bound together with the conductive material by a binder solution, and grows into particles having a specific range of specifications to form the core. A slurry including a solid electrolyte and a second conductive material is applied to the core to form a coating layer. The coating layer may be a single layer that covers the entire surface of the core, or may consist of multiple layers that cover only a portion of the core.
[0032] According to one embodiment of the present invention, the conductive material contained in the central portion and the conductive material contained in the coating layer have different specifications. The specifications refer to standards suitable for use in the central portion or the coating layer according to one embodiment of the present invention, and the specifications relate to, for example, size or shape. Here, the size or shape relates to the average diameter, aspect ratio, BET specific surface area, etc., which will be described below. In this specification, in order to distinguish between the conductive material contained in the central portion and the conductive material contained in the coating layer, the conductive material contained in the central portion is referred to as a first conductive material, and the conductive material contained in the coating layer is referred to as a second conductive material.
[0033] The first conductive material constitutes the center together with the active material and the binder, and serves as an electrical path for the active material located in the center of the sphere. The first conductive material may be uniformly dispersed so as to be in contact with most of the active material, and may be advantageous in improving the energy density of the electrode by reducing the amount of conductive material used. To achieve this object, according to one embodiment of the present invention, the first conductive material may be a cylindrical conductive material. The cylindrical shape may be deformed, such as bent, by external pressure. According to one embodiment of the present invention, the first conductive material has an average diameter of 10 nm to 30 nm. The average diameter is an arithmetic mean value of the diameter of a circle in the cylindrical shape, and is measured through particles distinguished in a SEM (Scanning Electron Microscope) image. Here, the circle is not limited to a perfect circle, but may be interpreted in a broad sense. Specifically, the average diameter of the first conductive material is 10 nm or more, 11 nm or more, 12 nm or more, 13 nm or more, 14 nm or more, 15 nm or more, and 30 nm or less, 29 nm or less, 28 nm or less, 27 nm or less, 26 nm or less, 25 nm or less, or may be 10 nm to 30 nm, 13 nm to 28 nm, or 15 nm to 25 nm. By using a relatively thin conductive material in the center, the volume of the conductive material in the granule can be reduced and the amount of active material can be increased.
[0034] According to one embodiment of the present invention, the first conductive material has an aspect ratio of 4000 to 6000. The aspect ratio is calculated by the following Equation 1, and the length of the major axis or minor axis used in Equation 1 is measured through particles distinguished in a SEM image.
[0035] [Formula 1] Aspect ratio = major axis length / minor axis length
[0036] Here, the "length of the long axis" means the longest perpendicular distance between two parallel tangents of the particle, and the "length of the short axis" means the shortest perpendicular distance between two parallel tangents of the particle. In a cylindrical shape, the length of the long axis may be the height, and the length of the short axis may be the diameter. The length of the long axis is equal to or longer than the length of the short axis, so that the aspect ratio has a value of 1 or more. Specifically, the aspect ratio of the first conductive material is 4000 or more, 4100 or more, 4200 or more, 4300 or more, 4400 or more, 4500 or more, and 6000 or less, 5900 or less, 5800 or less, 5700 or less, 5600 or less, 5500 or less, and may be 4000 to 6000, 4300 to 5800, or 4500 to 5500. The larger the aspect ratio, the more advantageous it is for the conductive material to form an electrical network inside the granule.
[0037] According to one embodiment of the present invention, the first conductive material has a BET specific surface area of 100 m 2 / g~300m 2 / g. The BET specific surface area is a specific surface area measured by the BET method, and can be calculated from the mass gas adsorption amount at liquid nitrogen temperature (77K) using, for example, BELSORP-mini II manufactured by BEL Japan. Specifically, the BET specific surface area of the first conductive material is 100 m 2 / g or more, 110m 2 / g or more, 120m 2 / g or more, 130m 2 / g or more, 140m 2 / g or more, 150m 2 / g or more, 300m 2 / g or less, 290m 2 / g or less, 280m 2 / g or less, 270m 2 / g or less, 260m 2 / g or less, 250m 2 / g or less, 100m 2 / g~300m 2 / g, 130m 2 / g~280m 2 / g, 150m 2 / g~250m 2Within the above range of BET specific surface area, the first conductive material can increase the accessibility to the active material and the solid electrolyte.
[0038] According to one embodiment of the present invention, the granules are spherical particles having a diameter of 30 μm to 150 μm. Here, the spherical particles do not mean perfectly spherical particles, so the diameter means the largest value among the distances from any one point on the particle surface to another point on the surface. Specifically, the diameter of the granules is 30 μm or more, 35 μm or more, 40 μm or more, 45 μm or more, 50 μm or more, 150 μm or less, 145 μm or less, 140 μm or less, 135 μm or less, 130 μm or less, 125 μm or less, 120 μm or less, or may be 30 μm to 150 μm, 40 μm to 135 μm, or 50 μm to 120 μm. The size of the granules in the above-mentioned range forms an appropriate level of voids in the granule layer, and helps the introduction of additional sulfide-based solid electrolyte and the change and movement of materials due to electrochemical reactions. The granule may comprise a core and a coating layer in the form of FIG. 1, the core occupying more than two-thirds of the diameter of the granule.
[0039] The electrode for an all-solid-state battery according to one embodiment of the present invention may be either a negative electrode or a positive electrode, and more specifically, the electrode for an all-solid-state battery may be a positive electrode.
[0040] When the electrode is a negative electrode, the electrode active material contained in the granules may be any material that can be used as a negative electrode active material for a lithium ion secondary battery. For example, the negative electrode active material may be carbon such as non-graphitizable carbon or graphite carbon; Li x Fe2O3(0≦x≦1), Li x WO2(0≦x≦1), Sn x Me 1-x Me' y O z(Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8), etc. metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc. One or more selected from may be used. According to one embodiment of the present invention, the negative electrode active material may contain a carbon-based material and / or Si.
[0041] When the electrode is a positive electrode, the electrode active material contained in the granule may be used without limitation as long as it can be used as a positive electrode active material of a lithium ion secondary battery. For example, the positive electrode active material may be a lithium transition metal oxide containing one or more transition metals. In one embodiment of the present invention, the positive electrode active material is LiCoO2, LiNiO2, LiMnO2, Li2MnO3, LiMn2O4, Li(Ni a Co b Mn c )O2(0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), LiNi 1-y Co y O2(0 < y < 1), LiCo 1-y Mn y O2(0 < y < 1), LiNi 1-y Mn y O2(0 < y < 1), Li(Ni a Co b Mn c )O4(0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-z Ni z O4(0 < z < 2), LiMn 2-z Co z O4(0 < z < 2) and is selected from the group consisting of combinations thereof.
[0042] The binder contained in the granules according to one embodiment of the present invention is mixed with the active material and the conductive material, which are fine particles in a powder state, and binds the components together to aid in particle growth. For example, since a sulfide-based solid electrolyte has moisture-sensitive properties, such as generating H2S gas when in contact with moisture, it is preferable to remove moisture as much as possible from the time of forming the granules. According to one embodiment of the present invention, the binder is an organic binder. The organic binder refers to a binder that dissolves or disperses in an organic solvent, particularly N-methylpyrrolidone (NMP), and is distinguished from an aqueous binder that uses water as a solvent or dispersion medium. Specifically, the organic binder may be selected from the group consisting of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyimide, polyamideimide, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butylene rubber, and fluororubber, but is not limited thereto.
[0043] According to one embodiment of the present invention, the active material is 85 wt% to 99.8 wt%, specifically 90 wt% to 99.5 wt%, more specifically 95 wt% to 99.0 wt%, the binder is 0.1 wt% to 10 wt%, specifically 0.5 wt% to 7.5 wt%, more specifically 1 wt% to 5 wt%, and the first conductive material is 0.1 wt% to 10 wt%, specifically 0.2 wt% to 5 wt%, more specifically 0.3 wt% to 1 wt% in the center. The contents of the active material, binder, and first conductive material are adjusted within the above-mentioned ranges, which is advantageous for improving the performance of the battery, and this may be due to the effect of reducing the content of the first conductive material due to the physical properties of the first conductive material.
[0044] According to one embodiment of the present invention, the core has a porosity of 10% to 40%. The porosity of the core means a volume ratio of voids in the granule, and the porosity can be measured, for example, using a mercury porosity analyzer (Autopore, Micromeritics), but is not limited thereto. Specifically, the porosity of the granule may be 10% or more, 15% or more, 20% or more, 25% or more, and 40% or less, 35% or less, 30% or less, or 10% to 40%, 15% to 35%, or 25% to 30%. If the porosity of the core is less than the above range, the sulfide-based solid electrolyte introduced from the coating layer or further is unlikely to come into close contact with the components in the core, and the improvement in battery performance may not be significant. If the porosity of the core exceeds the above range, the amount of active material is reduced compared to the volume of the core, and it is difficult to provide an electrode with a high loading of active material, and the improvement in battery performance may not be significant.
[0045] According to one embodiment of the present invention, the core is coated with a slurry containing a solid electrolyte and a second conductive material to form a coating layer. The coating layer covers at least a part or all of the surface of the core. In the coating layer, the solid electrolyte may be one or more selected from a polymer solid electrolyte and an inorganic solid electrolyte.
[0046] The polymer solid electrolyte may be a polymer solid electrolyte formed by adding a polymer resin to a solvated lithium salt, or may be an organic electrolyte solution containing an organic solvent and a lithium salt, an ionic liquid, a monomer or an oligomer, or a polymer gel electrolyte containing a polymer resin. According to one embodiment of the present invention, the lithium salt is an ionizable lithium salt, and Li + X - The anion of such a lithium salt is not particularly limited, but may be represented by F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4- , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , (CF3CF2SO2)2N - etc.
[0047] The solid polymer electrolyte may include, as a polymer resin, one or more substances selected from the group consisting of polyether-based polymers, polycarbonate-based polymers, acrylate-based polymers, polysiloxane-based polymers, phosphazene-based polymers, polyethylene derivatives, alkylene oxide derivatives, phosphate ester polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ionic dissociation groups, but are not necessarily limited thereto. In addition, the solid polymer electrolyte may include, as a polymer resin, one or more substances selected from the group consisting of branched copolymers in which amorphous polymers such as PMMA, polycarbonate, polysiloxane (pdms), and / or phosphazene are copolymerized with a comonomer on a PEO (polyethylene oxide) main chain, comb-like polymers, and crosslinked polymer resins, but are not necessarily limited thereto.
[0048] The inorganic solid electrolyte may include a sulfide-based solid electrolyte, a halide-based solid electrolyte, an oxide-based solid electrolyte, or at least one of these.
[0049] The sulfide-based solid electrolyte is an electrolyte component containing sulfur atoms, and is not limited to a specific component, and may include one or more of a crystalline solid electrolyte, a non-crystalline solid electrolyte (a glassy solid electrolyte), and a glass ceramic solid electrolyte. Specific examples of the sulfide-based solid electrolyte include an LPS-type sulfide containing sulfur and phosphorus, Li 4-x Ge 1-x P x S4 (x is 0.1 to 2, specifically x is 3 / 4, 2 / 3), Li 10±1 MP2X 12 (M=Ge,Si,Sn,Al,X=S,Se), Li 3.833 Sn 0.833 As 0.166 S4, Li4SnS4, Li 3.25 Ge 0.25 P 0.75 S4, Li2S-P2S5, B2S3-Li2S, xLi2S-(100-x)P2S5 (x is 70 to 80), Li2S-SiS2-Li3N, Li2S-P2S5-LiI, Li2S-SiS2-LiI, Li2S-B2S3-LiI and the like.
[0050] The halide-based solid electrolyte may include at least one of Li3YCl6 and Li3YBr6, but is not necessarily limited thereto.
[0051] The oxide-based solid electrolyte is, for example, Li 3x La 2 / 3-x LLT system with perovskite structure such as TiO3, Li 14 LISICON, Li such as Zn(GeO4)4 1.3 Al 0.3 Ti 1.7 LATP system such as (PO4)3, (Li 1+x Ge 2-x Al xThe LAGP system such as (PO4)3) and the phosphate system such as LiPON may be appropriately selected and used, but is not necessarily limited to these.
[0052] According to one embodiment of the present invention, the solid electrolyte includes a sulfide-based solid electrolyte.
[0053] The second conductive material forms a coating layer together with the solid electrolyte, and not only electrically connects the solid electrolyte in the coating layer, but also serves as a passage for the spherical center to electrically connect with other granules, other electrodes, solid electrolyte layers between electrodes, etc. The solid electrolyte in the coating layer may cause an electrical short circuit between active materials, but the presence of the second conductive material can solve such a short circuit problem. The second conductive material is preferably distributed thinly and uniformly in the coating layer to impart the above-mentioned functionality. To achieve this object, according to one embodiment of the present invention, the second conductive material may be a cylindrical conductive material. The cylindrical shape may be deformed, such as bent, by external pressure. According to one embodiment of the present invention, the second conductive material has an average diameter of 100 nm to 500 nm. The average diameter is measured in the same manner as the first conductive material. Specifically, the average diameter of the second conductive material is 100 nm or more, 110 nm or more, 120 nm or more, 130 nm or more, 140 nm or more, 150 nm or more, and 500 nm or less, 480 nm or less, 460 nm or less, 440 nm or less, 420 nm or less, 400 nm or less, or may be 100 nm to 500 nm, 130 nm to 460 nm, or 150 nm to 400 nm. By using a relatively thick conductive material in the coating layer, it is possible to impart only the necessary functionality for conductivity without causing side reactions in relation to the solid electrolyte.
[0054] According to one embodiment of the present invention, the second conductive material has an aspect ratio of 100 to 300. The aspect ratio is measured in the same manner as the first conductive material. Specifically, the aspect ratio of the second conductive material is 100 or more, 110 or more, 120 or more, 130 or more, 140 or more, or 150 or more, and is 300 or less, 290 or less, 280 or less, 270 or less, 260 or less, or 250 or less, and may be 100 to 300, 130 to 280, or 150 to 250. If the aspect ratio is too large, problems such as aggregation between conductive materials may occur, and it is preferable to adjust the aspect ratio to an appropriate level in order to uniformly disperse the second conductive material in the coating layer.
[0055] According to one embodiment of the present invention, the second conductive material has a BET specific surface area of 10 m 2 / g~30m 2 / g. The BET specific surface area is measured in the same manner as the first conductive material. Specifically, the BET specific surface area of the second conductive material is 2 / g or more, 11m 2 / g or more, 12m 2 / g or more, 13m 2 / g or more, 14m 2 / g or more, 15m 2 / g or more, 30m 2 / g or less, 29m 2 / g or less, 28m 2 / g or less, 27m 2 / g or less, 26m 2 / g or less, 25m 2 / g or less, 10m 2 / g~30m 2 / g, 13m 2 / g~28m 2 / g, 15m 2 / g~25m 2 If the specific surface area is too large, problems such as side reactions with the solid electrolyte may occur, and therefore, in order to achieve only the intended functionality of electrical conductivity in the coating layer, it is preferable to adjust the specific surface area to an appropriate level.
[0056] The first conductive material and the second conductive material may be any conductive material commonly used in the technical field without any particular limitation as long as they satisfy the above-mentioned standards. According to one embodiment of the present invention, the first conductive material includes carbon nanotubes. According to one embodiment of the present invention, the second conductive material includes carbon nanofibers.
[0057] According to one embodiment of the present invention, the weight ratio of the solid electrolyte in the coating layer is 15 wt% to 40 wt% based on the total weight of the granule. Specifically, the weight ratio of the solid electrolyte is 15 wt% or more, 16 wt% or more, 17 wt% or more, 18 wt% or more, 19 wt% or more, or 20 wt% or more, and 40 wt% or less, 39 wt% or less, 38 wt% or less, 37 wt% or less, 36 wt% or less, or 35 wt% or less, and may be 15 wt% to 40 wt%, 18 wt% to 38 wt%, or 20 wt% to 35 wt%. When the solid electrolyte is introduced into the coating layer within the above range, the connectivity with the solid electrolyte outside the granule can be further improved.
[0058] According to one embodiment of the present invention, the weight ratio of the second conductive material in the coating layer is 0.01% by weight to 1% by weight based on the total weight of the granules. Specifically, the weight ratio of the second conductive material is 0.01% by weight or more, 0.02% by weight or more, 0.03% by weight or more, and 1% by weight or less, 0.9% by weight or less, 0.8% by weight or less, 0.7% by weight or less, 0.6% by weight or less, 0.5% by weight or less, and may be 0.01% by weight to 1% by weight, 0.02% by weight to 0.8% by weight, or 0.03% by weight to 0.5% by weight. When the second conductive material is introduced into the coating layer within the above range, the connectivity between the active materials can be further improved.
[0059] The first conductive material, which is directly mixed with the active material in the granule, may be contained in a larger amount than the second conductive material. According to one embodiment of the present invention, the weight ratio of the first conductive material to the second conductive material is 5:1 to 30:1. Specifically, the weight ratio of the first conductive material to the second conductive material is 5:1 or more, 5.5:1 or more, 6:1 or more, and 30:1 or less, 25:1 or less, 20:1 or less, and may be 5:1 to 30:1, 5.5:1 to 25:1, or 6:1 to 20:1. Within the above range, the effect of introducing the conductive material separately into the center and the coating layer may be further added.
[0060] The coating layer is formed by coating a coating material including a solid electrolyte and a second conductive material on the central portion, and the coating method may be any of various methods used in the art. According to one embodiment of the present invention, the coating layer is formed by coating the central portion using a mechanofusion method. The mechanofusion method can apply high shear force to the coating layer, and thus the coating layer can be formed thin and uniform. In addition, the high shear force of the mechanofusion method is advantageous for a sulfide-based solid electrolyte, which has a relatively small particle size compared to the second conductive material, to easily penetrate into the voids in the central portion and form an electrical network within the granules.
[0061] An electrode for an all-solid-state battery according to an embodiment of the present invention is manufactured by loading granules onto a current collector to form a sheet-shaped granule layer. In this case, the current collector is electrically conductive, such as a metal plate, and an electrode known in the art may be appropriately used according to the polarity of the battery. Since the granules constituting the granule layer each include a coating layer containing a solid electrolyte and a second conductive material, a sufficient electrical network can be formed between the granules constituting the granule layer, and the electrical network can be supplemented by impregnating the gaps between the granule layers with a solid electrolyte and drying the solid electrolyte. Furthermore, the supplemented solid electrolyte may be a sulfide-based solid electrolyte, as in the coating layer, which can reduce resistance in the battery and contribute to improving battery performance.
[0062] According to one embodiment of the present invention, in the all-solid-state battery electrode, the electrode active material layer has a thickness of 100 μm to 300 μm. Here, the electrode active material layer means a sheet-like layer applied on the current collector, excluding the current collector, when the current collector is used in the manufacture of the electrode, and the electrode active material layer contains the above-mentioned granules and a solid electrolyte that is filled into the gaps between the granules as necessary. Specifically, the thickness of the electrode active material layer is 100 μm or more, 110 μm or more, 120 μm or more, 130 μm or more, 140 μm or more, 150 μm or more, and 300 μm or less, 290 μm or less, 280 μm or less, 270 μm or less, 260 μm or less, 250 μm or less, and may be 100 μm to 300 μm, 120 μm to 270 μm, or 150 μm to 250 μm. If the thickness of the electrode active material layer is less than the above range, the loading amount of the active material may decrease, and the improvement in battery performance may not be significant. If the thickness of the electrode active material layer exceeds the above range, the durability of the electrode may decrease, and the improvement in battery performance may not be significant.
[0063] In one aspect of the present invention, an all-solid-state battery is provided that includes the above-mentioned all-solid-state battery electrode as a positive electrode and / or a negative electrode. In constructing the all-solid-state battery, in addition to the solid electrolyte contained in the electrode, a separate solid electrolyte layer may be introduced between the positive electrode and the negative electrode, and such a solid electrolyte layer may also function as a separator in a general lithium secondary battery. The above-mentioned electrode may be used together with a liquid electrolyte in some cases to be used as a semi-solid-state battery, in which case a separate polymer separator may be further required.
[0064] The polymer separator is interposed between the negative electrode and the positive electrode, and serves to electrically insulate the negative electrode from the positive electrode while allowing lithium ions to pass through. The polymer separator may be any polymer separator membrane used in the field of general all-solid-state batteries, and is not particularly limited.
[0065] In one aspect of the present invention, there is provided a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0066] Specific examples of the device include, but are not limited to, power tools that are powered by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.
[0067] Preferred examples are shown below to aid in understanding the present invention. The following examples are provided to facilitate understanding of the present invention, and the present invention is not limited thereto.
[0068] Manufacturing example: Manufacturing granules containing active materials Manufacturing Example 1 LiNi as active material 0.6 Co 0.2 Mn 0.2 O2 (NCM 622), carbon nanotubes (average particle size: approx. 15 nm, aspect ratio: approx. 5000, BET specific surface area: approx. 150 m) as the first conductive material. 2 The active material was mixed with polyvinylidene fluoride (PVDF) as a binder in a weight ratio of 96.7:0.3:3 (active material:conductive material:binder) in N-methylpyrrolidone solvent to prepare a slurry, which was then spray-dried to prepare a core portion with a diameter of approximately 60 μm (porosity: approximately 30%).
[0069] The sulfide-based solid electrolyte was Li2S-P2S5, and the second conductive material was carbon nanofiber (diameter: approx. 250 nm, aspect ratio: approx. 200, BET specific surface area: approx. 20 m 2The mixture of 0.15g / g was then run in a mechanofusion device (manufacturer: Hosokawa Micron, product: Nobilta NOB-130) at 3,000 rpm for 10 minutes together with the produced core to produce granules with a diameter of about 70 μm on which a coating layer was formed. The solid electrolyte content in the granules was about 25 wt %, and the second conductive material content was about 0.03 wt %.
[0070] Comparative Manufacturing Example 1 The core was manufactured in the same manner as in Manufacturing Example 1, except that when forming the coating layer, only the sulfide-based solid electrolyte was used without the second conductive material. Comparative Manufacturing Example 2 Granules were produced in the same manner as in Production Example 1, except that when forming the coating layer, the second conductive material was the same as the first conductive material (center: first conductive material, coating layer: first conductive material).
[0071] Comparative Manufacturing Example 3 Granules were produced in the same manner as in Production Example 1, except that the first conductive material was the same as the second conductive material when producing the core (core: second conductive material, coating layer: second conductive material).
[0072] Example: Manufacture of electrodes and batteries containing the produced granules Example 1 The granules prepared in Preparation Example 1 were applied to one side of an aluminum current collector, rolled and dried to prepare a positive electrode having a thickness of about 130 μm (sulfide-based electrolyte was about 20% by weight of the granules). Li2S-LiCl-P2S5 was mixed with a polyvinylidene fluoride (PVDF) solution (a solution in which PVDF and toluene were mixed in a weight ratio of 8:92) to prepare a slurry, which was then applied to a thickness of about 100 μm on a lithium foil (Li foil) having a thickness of about 50 μm to prepare a solid electrolyte and a negative electrode including the same. The positive and negative electrodes were stacked and pressed to prepare an electrode assembly, which was then placed inside a battery case to prepare an all-solid-state battery.
[0073] Comparative Example 1 An all-solid-state battery was manufactured in the same manner as in Example 1, except that the granules manufactured in Comparative Preparation Example 1 were used instead of Preparation Example 1 when manufacturing the positive electrode.
[0074] Comparative Example 2 An all-solid-state battery was manufactured in the same manner as in Example 1, except that the granules manufactured in Comparative Preparation Example 2 were used instead of Preparation Example 1 when manufacturing the positive electrode.
[0075] Comparative Example 3 An all-solid-state battery was manufactured in the same manner as in Example 1, except that the granules manufactured in Comparative Preparation Example 3 were used instead of Preparation Example 1 when manufacturing the positive electrode.
[0076] Experimental Example: Evaluation of Manufacturing Examples and Working Examples Experimental example 1: Battery performance evaluation The batteries of Example 1 and Comparative Examples 1 to 3 were discharged at 0.1 C and 1.0 C, respectively, and the initial coulombic efficiency (0.1 C charge / discharge) and the discharge capacity ratio (1.0 C discharge capacity / 0.1 C discharge capacity×100, %) were measured. The results are shown in Table 1 below.
[0077] [Table 1]
[0078] According to Table 1, the battery of Example 1 (first conductive material (core)-second conductive material (coating layer)) did not show any particular decrease in battery performance even under higher C-rate conditions, whereas the battery performance of Comparative Example 1 (first conductive material (core)), Comparative Example 2 (first conductive material (core)-first conductive material (coating layer)) and Comparative Example 3 (second conductive material (core)-second conductive material (coating layer)) significantly decreased under higher C-rate conditions.
[0079] All mere variations and modifications of the present invention belong to the scope of the present invention, and the specific scope of protection of the present invention will be apparent from the appended claims. [Explanation of symbols]
[0080] 10: Center 20: Coating layer 100: Granules
Claims
1. a core including an active material, a first conductive material, and a binder; the coating layer is located on an outer side of the core and includes a granule having a solid electrolyte and a second conductive material; The electrode for an all-solid-state battery, wherein the first conductive material and the second conductive material have different sizes or shapes.
2. The electrode for an all-solid-state battery according to claim 1 , wherein the first conductive material has an average diameter of 10 nm to 30 nm.
3. The first conductive material has an aspect ratio of 4000 to 6000 and a BET specific surface area of 100 m 2 / g to 300m 2 The electrode for an all-solid-state battery according to claim 1 , wherein the molecular weight of the electrode is 1000 or more.
4. The electrode for an all-solid-state battery according to claim 1 , wherein the second conductive material has an average diameter of 100 nm to 500 nm.
5. The second conductive material has an aspect ratio of 100 to 300 and a BET specific surface area of 10 m 2 / g to 30m 2 The electrode for an all-solid-state battery according to claim 1 , wherein the molecular weight of the electrode is 1000 or more.
6. The electrode for an all-solid-state battery according to claim 1 , wherein the first conductive material comprises a carbon nanotube.
7. The electrode for an all-solid-state battery according to claim 1 , wherein the second conductive material includes carbon nanofibers.
8. The active material is a positive electrode active material, The positive electrode active material is LiCoO 2 , LiNiO 2 , LiMnO 2 , Li 2 MnO 3 , LiMn 2 O 4 , Li(Ni a Co b Mn c ) O 2 (0<a<1, 0<b<1, 0<c<1, a+b+c=1), LiNi 1-y Co y O 2 (0<y<1), LiCo 1-y Mn y O 2 (0<y<1), LiNi 1-y Mn y O 2 (0<y<1), Li(Ni a Co b Mn c ) O 4 (0<a<2, 0<b<2, 0<c<2, a+b+c=2), LiMn 2-z Ni z O 4 (0<z<2), LiMn 2-z Co z O 4 The electrode for an all-solid-state battery according to claim 1 , wherein z is selected from the group consisting of (0<z<2) and combinations thereof.
9. The electrode for an all-solid-state battery according to claim 1 , wherein the solid electrolyte includes a sulfide-based solid electrolyte.
10. The electrode for an all-solid-state battery according to claim 1, wherein the granules are spherical particles having a diameter of 30 μm to 150 μm.
11. 2. The electrode for an all-solid-state battery according to claim 1, wherein a weight ratio of the solid electrolyte in the coating layer is 15% by weight to 40% by weight based on the total weight of the granules.
12. 2. The electrode for an all-solid-state battery according to claim 1, wherein a weight ratio of the second conductive material in the coating layer is 0.01% by weight to 1% by weight based on the total weight of the granules.
13. 2. The electrode for an all-solid-state battery according to claim 1, wherein the core comprises 85 wt % to 99.8 wt % of an active material, 0.1 wt % to 10 wt % of a binder, and 0.1 wt % to 10 wt % of a first conductive material, based on a total weight of the core.
14. The electrode for an all-solid-state battery according to claim 1, wherein a weight ratio of the first conductive material to the second conductive material is 5:1 to 30:
1.
15. The electrode for an all-solid-state battery according to claim 1 , wherein the coating layer is formed by coating on the center portion using a mechanofusion method.
Citation Information
Patent Citations
Cathode material for nonaqueous electrolyte lithium ion battery, and battery using the same
JP2007048525A
Positive electrode for lithium ion secondary battery and lithium ion secondary battery
JP2018097961A
Granulated particle for lithium secondary battery positive electrode and method for producing same, mixed ink, and lithium secondary battery
WO2013168785A1
KR2016-0146737